Computer science open dissertations [electronic resource] - American Doctoral Dissertations; BiblioLabs; EBSCO Host.; The H.W. Wilson Foundation; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Birmingham, AL eBSCO Industries, Inc, 2020)
The channels by which today?s scholars discover relevant content are varied and wide. In this increasingly complex environment, institutions are seeking strategies to make their students? theses and dissertations as widely visible and cited as possible. With EBSCO Open Dissertations, institutions and students are offered an innovative approach to meeting these goals by driving additional traffic to ETDs in institutional repositories. The program is free for authors and participating institutions with the desired end of making significant open-access content more readily discoverable to end-users within and beyond academic institutions.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; Computer science -- Dissertations, Academic -- Open educational resources -- Electronic information resources